(untitled) (Journal Nutrizione, 2025)
This study evaluates the implementation of Indonesia’s Makan Bergizi Gratis programme delivered through correctional kitchens, focusing on nutritional outcomes, consumer satisfaction and the governance environment shaping programme performance. A convergent mixed-methods design was used to assess anthropometric indicators, haemoglobin levels and structured satisfaction responses among school beneficiaries, complemented by qualitative inquiry with correctional kitchen staff and production supervisors. The findings show that while caloric adequacy is generally achieved, the meals remain low in micronutrient density, leading to persistent risks of iron deficiency and limited improvements in height-for-age indicators. Beneficiary satisfaction results highlight concerns regarding taste, menu monotony, hygiene, temperature consistency and cultural alignment, which collectively reduce meal acceptance and contribute to plate waste. Governance analysis reveals systemic constraints including rigid procurement rules, insufficient cross-sector coordination, weak monitoring mechanisms and limited training for inmate food handlers and correctional personnel. These structural factors shape the quality, safety and acceptability of meals produced in correctional kitchens and limit their compliance with national nutrition standards. The study concludes that while correctional kitchens can support MBG delivery, significant institutional strengthening is required through improved procurement flexibility, facility upgrades, clearer regulatory alignment and stronger human resource capacity. Enhancing these governance dimensions is essential to ensure nutritionally adequate, safe and socially acceptable MBG service delivery for schoolchildren